Multiple Antibiotic-Resistant Bacteria Resistant to Electrochemical Disinfection with Variation of Key Antibiotic Resistance Genes - Jiang, Kaiyang; Hongna Li; Liu, Wen; Yi Jiang; Zhiguo Zhang; Ju, Feng; Song, Tingting; Binxu Li; Wang, Xuerong; Changxiong Zhu (ACS ES&T Water, 2023)
Electrochemical disinfection (ED) is effective in removal of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) during wastewater treatment. However, the inner relationship of antibiotic-resistant phenotypes with their genotypes of ARB is still unclear in the ED process. This study explored the disinfection mechanism at the microcosmic level using four Escherichia coli (E. coli) strains with different antibiotic-resistant phenotypes. Results showed that bacteria with multiple antibiotic resistance tended to have stronger viability in disinfection compared with those resistant to fewer antibiotics. Interestingly, antibiotic-resistant phenotypes changed little in the disinfection process, while genotypes closely responded to bacterial resistance of different E. coli. In detail, beta-lactamase resistance genes played a leading role in the cross-resistance between antibiotics and electrochemical oxidation. They were proved to reduce oxidative destruction by increasing the strength of the cell wall and membrane. In addition, diaminopyrimidine and macrolide-lincosamide-streptogramin B resistance genes are also closely related to the bacterial resistance to ED. Combined with the quantitative determination of ARGs, the abundance of IntI1 and aminoglycoside resistance genes can be regarded as indicators for the risk of cross-resistance to antibiotics and electrochemical oxidation. This study provided important references for in depth understanding and accurate control of antibiotic resistance with advanced oxidation processes.